Pengaruh Model Pembelajaran Think Talk Write (TTW) dan Motivasi Belajar Terhadap Keterampilan Menulis Pantun di Kelas IV Sekolah Dasar - Sholihah, Nurul; Slamet, St; Widianto Atmojo, Idam (Universitas Sebelas Maret, 2020)
The purpose of this research is to finds out the effect of Think Talk Write (TTW)model and learning motivation on pantun writing skill. This form of research is a quasiexperimental. The population in this research is the fourth grades students of Public Elementary School in Laweyan district. Sampling techniques is using cluster random sampling. Data collection techniques are using tests and questionnaire. Data analysis technique is using two ways anova. The results revealed that the Think Talk Write (TTW) model give a positive effect on pantun writing skill (FA = 6,55 > Ftabel = 4,09), the learning motivation give a positive effect on pantun writing skill (FB = 45,74 > Ftabel = 4,09), and there is interaction between model of learning and learning motivation on pantun writing skill (FAB = 4,17 > Ftabel = 4,09). Based on the result of the research, it can be concluded that the Think Talk Write (TTW) model and learning motivation give a positive effect on pantun writing skill.